The Influence Of The Project Based Learning Model On The Understanding Of Islamic Religious Education Learning In Class 5 Students At SD Plus Mutiara Insani Purwakarta - Alifia Rahma Hidayat; Dede Supendi; Dyah Wulandari (IJGIE (International Journal of Graduate of Islamic Education), 2024)
Based on the results of interviews with Islamic Religious Education teachers, there were several problems that hindered the Ramadhan fasting factor on students' understanding, including: there were still some students whose PAI understanding scores were below the KKM, method Less innovative learning makes students bored of learning PAI, there are still some students who don't understand PAI learning using conventional methods. The aim of this research is to determine the effect of the Project Based Learning learning model on the understanding of PAI learning for grade 5 students at SD Plus Mutiara Insani Purwakarta. The theory used in understanding learning is Bloom's Taxonomy, where the indicators are divided into 3 domains, namely: cognitive, affective and psychomotor. This research method uses a quantitative experimental method, with a Probability Sampling sampling technique. The number of samples used as respondents is 30. Based on the results of research and data analysis, it shows that the Project Based Learning learning model and lecture method have a significant influence, this is shown by the average or mean T-Test results using the lecture method around 55.41, while using the Project Based Learning learning model around 55.41. 78.96, then there is an influence between the results of students' understanding of learning using the lecture method and the Project Based Learning learning model, shown by an increase in the results of learning understanding around 23%. This was strengthened again by significant results, namely the sig value. (2-tailed) with a value of 0.000 < 0.361.The Pretest average with a percentage of 31.96% is in the not good category, while the Posttest average with a percentage of 70.38% is in the good category. Therefore, it can be concluded that there is an influence between the Project Based Learning learning model and the lecture method on increasing the results of understanding PAI learning for grade 5 students at SD Plus Mutiara Insani Purwakarta using the Project Based Learning learning model and the lecture method.